Study of Weak Continuous Functions with Separation Axioms in Bitopological Spaces - Hend M. Bouseliana (African Journal of Advanced Pure and Applied Sciences, 2023)
The purpose of this work to set the notion of weak continuity in bitopology. Its characterizations and fundamental properties are introduced. The major conclusions bear on the concept of weakly continuous functions in Bitopological settings. Also, the implication of some separation axioms is investigated. Additionally, the attitude of p-weak continuity with pairwise Urysohn and pairwise connectedness spaces is studied.